Defect‐Expedited Photocarrier Separation in Zn2In2S5 for High‐Efficiency Photocatalytic C─C Coupling Synchronized with H2 Liberation from Benzyl Alcohol - Ma, Minmin; Wang, Ran; Shi, Li; Li, Ronghua; Huang, Jie; Li, Zhuo; Li, Peng; Konysheva, Elena Yu; Li, Yanbo; Liu, Gang; Xu, Xiaoxiang (Advanced functional materials, 2024)
Photocatalytic carbon‐carbon (C─C) coupling of benzyl alcohol is a promising means to coproduce the value‐added chemicals with H2 but is generally subject to low efficiency in terms of photon utilization. Here, efficient benzyl alcohol C─C coupling is achieved over Zn2In2S5 containing a tunable content of Zn vacancies (VZn). The VZn tends to form shallow defect states below the conduction band that can expedite photocarrier separation by collecting the photo‐generated electrons. The VZn‐collected electrons are essential for a high selectivity of the C─C coupling reactions because they enable a fast elimination of the byproduct benzaldehyde by catalyzing its reduction back to the ketyl radicals. Under simulated sunlight, the VZn‐containing Zn2In2S5 accomplishes ≈100% conversion of benzyl alcohol for merely 1 h and attains ≈100% selectivity for the C─C coupling compounds for 2 h, delivering an apparent quantum yield as high as 7.7% at 420 ± 20 nm. The benefits of VZn have also been verified by the theoretical calculations that indicate reduced energy barriers for various surface reactions in the presence of VZn. This work brings fresh mechanistic insights into the role of VZn and can serve as a useful guideline in the design of efficient photocatalysts. Zn2In2S5 with a tunable content of zinc vacancies is prepared. The zinc vacancies form shallow defect states below the conduction band that can expedite photocarrier separation and help to eliminate the byproduct benzaldehyde during photocatalytic C─C coupling reactions of benzyl alcohol, contributing to high reaction efficiency with a selectivity of unity.